Economic potential and marketing trend of bamboo in Nepal: A case study from Rautahat District - Jha, R. K.; Yadav, J. N. (Banko Janakari, 2015)
Bamboo is a versatile gift of nature. It has direct link to the socio-economic and cultural conditions of the Nepalese people. The aim of the study was to assess the status of bamboo production in private land, its contribution to socio-economic condition and marketing trend of bamboo culms and bamboo products. This study was conducted in 10 Village Development Committees (VDCs) of Rautahat District during July to October, 2010. Data were collected through household (HH) survey using semi-structured questionnaires, key-informant survey through interviews, focus group discussion, market survey, and bamboo stock measurement. Two wards in each VDC were selected purposively based on availability of bamboo. The HHs in the selected wards were categorized into three well-being classes (rich, middle and poor) through participatory approach. The average number of bamboo clumps per HH was found to be 3.4 in the three categories of HHs within the study area; 5.7 (highest) in the rich-class HHs followed by 3.9 in the middle-class HHs and 0.5 (lowest) in the poor-class HHs; there were, on an average, 80 culms per bamboo clump in the study area. On the contrary, the income from the bamboo sector was found to be just opposite- 73.85% in the poor-class HHs followed by 2.37% in the middle-class HHs and 0.85% in the rich-class HHs. The prices of bamboo culms, basket and Nanglo winnow were found to have increased by 51.6%, 41.0% and 36.4% respectively during the last 4 years- from 2006/07 to 2010. No fixed market, no fixed price and no guarantee in sealing the products were found to be the major problems for market development of the bamboo products in the district. Awareness-raising through trainings and study-tours on plantation techniques to the bamboo-growers as well as the craft-makers and production of high-prized products are essential for increasing bamboo plantations and for the development of bamboo market in the district so as to make bamboo-culm supplier in the near future. The findings of this study will help the concerned agencies to inform about the status and future prospects of bamboo sector in the district. Banko Janakari; A Journal of Forestry Information for Nepal Vol. 25, No. 1 Page: 63-75